HOW TO PREDICT THE BLOOMING OF THE GIANT CORPSE INFLORESCENCE Amorphophallus titanum (Becc.) Becc. ex Arcang [Prediksi Mekarnya Bunga Bangkai Raksasa Amorphophallus titanum (Becc.) Becc. ex Arcang] - Latifah, Dian; Wawangningrum, Hary; Hartini, Sri; Munawaroh, Esti (Research Center for Biology-Indonesian Institute of Sciences, 2015)
The giant corpse inflorescence (Amorphophallus titanum) is native to Indonesia. It is one of the flagships of The Center for Plant Conservation Bogor Botanic Gardens, Indonesian Institute of Sciences (LIPI) to raise public awareness for saving plants from extinction and caring the living environment. The blooming of the giant inflorescence attracts many visitors. Therefore, one of the research focuses of Amorphophallus titanum is how to predict the blooming-time in order to inform visitors earlier. The results of this study can be used as the basic information to predict the blooming of the inflorescences. Previous researchers had tried to predict the blooming based on firstly, the differential diagnostics of an inflorescence bud and leaf bud, and secondly, the growth pattern of the flowering bud from one individual sample only; whereas, our results suggested new findings. In this research, the prediction was examined from 2011-2012 on five individual samples planted in Bogor Botanic Gardens. We suggested that (1) the differential diagnostics of an inflorescence bud and leaf bud were not only based on the early bud shapes but also the growth rate, and (2) our results supported Lobin?s findings by providing a statistical formula for growth pattern of the flowering bud.